The Heterogeneous Effects of HIV Testing - Baird, Sarah; Gong, Erick; McIntosh, Craig; Özler, Berk (Elsevier, 2014)
An extensive multi-disciplinary literature examines the effects of learning one's HIV status on subsequent risky sexual behaviors. However, many of these studies rely on non-experimental designs; use self-reported outcome measures; or both. In this study, we investigate the effects of a randomly assigned home based HIV testing and counseling (HTC) intervention on risky sexual behaviors and schooling investments among school-age females in Malawi. We find no overall effects on HIV, Herpes Simplex Virus (HSV-2), or achievement test scores at follow-up. However, among the small group of individuals who tested positive for HIV, we find a large increase in the probability of HSV-2 infection, with this effect being stronger among those surprised by their test results. Similarly, those surprised by HIV-negative test results have significantly higher achievement test scores at follow-up, consistent with increased returns to investments in human capital.